The interface between health, climate change and land use in Brazil: analyzing the evolution of international scientific production between 1990 and 2019 - Abreu, Alexandre Maduro; Sátiro, Guadalupe; Litre, Gabriela; Santos, Luciana dos; Oliveira, Jessica Eloísa de; Soares, Danny; Ávila, Kayton (Saúde e Sociedade, 2020)
This bibliographic study analyzes the evolution of international scientific production concerning the interface between health, climate change and land use in the last decades, emphasizing the understanding of health in its broad sense, highlighting the environmental, social and climate dimensions by assessing publications indexed in the Scopus database. To achieve this objective, two methodologies were applied: (1) a descriptive-analytical systematic review of the international literature, incorporating qualitative and quantitative methods; (2) and network analysis based on the categorization of keyword dynamics using the application software VOSviewer. Applying search filters to the database resulted in 283 articles, where 162 articles represent the health and climate change interface, 86 represent the health and land use interface, 13 the land use and climate change interface, and the last 22 included all three. There has been a growing increase in the number of publications in the last decade, especially 2008, 2014 and 2018. The use of multivariate methodologies is prevalent, namely (i) ecological niche modeling; (ii) maximum entropy niche modeling; (iii) life cycle assessment; (iv) analysis of sentinel areas; (v) multiple residue analysis; (vi) remote sensing; (vii) linear regression analysis, among others, which show the existence of multiple drivers and vulnerabilities when dealing with the relation between climate change, health and land use. The biggest challenge in aggregating socioenvironmental, climatic and epidemiological variables is the availability of primary and secondary data on a municipal scale with national coverage and a time series of at least 20 years.